Evaluasi Mutu Tablet Parasetamol Generik yang Beredar di Wilayah Purwokerto - Herline, Fitri; Susilowati, Sri Sutji; Kurniawan, Dhadhang Wahyu (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Paracetamol or acetaminophen is a drug that can be used to reduce fever. Paracetamol also be used for headaches and minor aches. This study aimed to determine the physical conditions and dissolution rate of generic paracetamol tablets that were circulating in Purwokerto. The method of this research is experimental with the samples of generic paracetamol tablets that were circulating in Purwokerto. Evaluation of generic paracetamol tablets were including the size uniformity, weight uniformity, hardness, friability, disintegration, assay, and dissolution test. Dissolution testing is carried out by a paddle type at 50 rpm. Dissolution medium used phosphate buffer pH 5.8 ± 0.5 up to 900 mL. Samples obtained from minutes to 5, 10, 15, 20, 30, 45, and 60 were measured absorbance in the UV-Vis spectrophotometer at a wavelength of maximum paracetamol (243 nm). The dissolution data disclosure were seen through the concentration at t = 30 min and paracetamol tablets at t = 30 minutes, not less than 85%. The data were analyzed descriptively and compared with tablets requirements according to the Indonesian Pharmacopoeia and other libraries. The results showed that the generic Paracetamol tablets meet the requirements according to Indonesia Pharmacopoeia. That were including the size uniformity, weight uniformity, hardness, friability, disintegration, and assay. Dissolution test for all generic Paracetamol tablets meet the requirements of 85%.